Astrocyte activation and capillary remodeling in modified bilateral common carotid artery occlusion mice. (August 2017) - Song, Jiangman; Nan, Di; He, Qihua; Yang, Lu; Guo, Huailian
Abstract: Objective: The cerebral ischemia leads to brain dysfunction with neuron degeneration and responses from astrocytes and vessels. The aim of this study was to study the changes of astrocyte and microvessel in modified BCCAO mice. Methods: Adult transgenic Tie2‐GFP mice were subjected to modified BCCAO operation and cranial window implantation. CBF and neurological injury were examined after ischemia. Astrocytes and vessels were investigated by two‐photon laser‐scanning microscope and confocal laser‐scanning microscope in vivo. Results: The CBF decreased to approximately 40% of the baseline in the ischemic mice ( P <.05). The neuron damage was explicit after the cerebral ischemia ( P <.05), while no significant impairment of the motor and cognitive function was detected ( P >.05). The density of astrocyte and volume of the astrocyte soma was increased significantly after ischemia ( P <.01). Meanwhile, the mean distance between the penetrating artery and the nearest astrocyte soma decreased significantly ( P <.01). Besides, the increased diameter of capillary and change of vessel arrangement were observed. Conclusion: The cerebral ischemia was successfully induced by this modified BCCAO model. Astrocyte activation and the capillary remodeling, including dilution of capillary and tortuosity, were observed in this model.